1993
DOI: 10.3354/dao017067
|View full text |Cite
|
Sign up to set email alerts
|

Isolates of viral hemorrhagic septicemia virus from North America and Europe can be detected and distinguished by DNA probes

Abstract: Biotinylated DNA probes were constructed to hybndize with speclfic sequences within the messenger RNA (mRNA) of the nucleoprotein (N) gene of vlral hemorrhagic septicemia virus (VHSV) reference strains from Europe (07-71) and North Arnenca (Makah) Probes were synthesized that were complementary to (1) a 29-nucleotide sequence near the center of the N gene conlmon to both the 07-71 and Makah reference strains of the virus (2) a unique 28-nucleotide sequence that followed the open r e a d n g frame of the Makah … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 9 publications
2
22
0
Order By: Relevance
“…Nevertheless, more data (e.g. molecular comparison with continental pathogenic strains) is necessary to confirm this hypothesis.It has been reported that VHSV isolates from North America and Europe constituted 2 genetically distinct groups of the virus (Batts et al 1993, Basurco et al 1995, Einer-Jensen et al 1995, Benmansour et al 1997). Further analysis is necessary to determine the relatedness between the Greenland halibut isolates and the European and/or North American strains.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, more data (e.g. molecular comparison with continental pathogenic strains) is necessary to confirm this hypothesis.It has been reported that VHSV isolates from North America and Europe constituted 2 genetically distinct groups of the virus (Batts et al 1993, Basurco et al 1995, Einer-Jensen et al 1995, Benmansour et al 1997). Further analysis is necessary to determine the relatedness between the Greenland halibut isolates and the European and/or North American strains.…”
mentioning
confidence: 99%
“…Previous studies using antisera against that strain (4 neutralizing MAbs against the viral glycoprotein and 1 polyclonal antisera) have demonstrated antigenic diversity among European isolates of VHSV, establishing 3 reaction patterns but only 1 major serotype (Olesen et al 1993). Although distinguishable from the European strains by genotyping with molecular techniques (Batts et al 1993, Einer-Jensen et al 1995, Benmansour et al 1997, Snow et al 1999, all North American isolates of VHSV isolated in the Pacific coast, from either salmonids or marine fishes, have been identified as Type F1 strains using the plaque neutralization test and IFAT with a polyclonal antisera (Meyers et al 1992, Meyers & Winton 1995. Therefore, having regard to the location of the area where the fish were caught, and the serological techniques used, most of the Greenland halibut VHSV isolates would be expected to be of the F1 type.…”
mentioning
confidence: 99%
“…If CPE were observed, a second passage from the affected cell culture was performed to confirm CPE. Initial virus identity for isolates prior to 1998 was determined using a DNA probe (Batts et al 1993), while isolations post 1998 were confirmed via VHSV-specific reverse transcriptase polymerase chain reaction (RT-PCR) as described below. All BC VHSV isolates listed herein were cultured with the exception of the Pa cific Hake isolate which was detected via quantitative RT-PCR (RT-qPCR) (Garver et al 2011) and RT-PCR.…”
Section: Virus Isolation and Fish Lossesmentioning
confidence: 99%
“…Further surveillance is needed to determine the extent of VHSV in differed by about 13%. Similarly, Batts et al (1993) these species, and studies to determine the virulence showed that a DNA probe designed to hybridize with a of both strains of the virus for marine fishes seem unique sequence in the N gene of the Makah isolate warranted. reacted with all North American and none of the Many RNA viruses, including rhabdoviruses, are European isolates tested, while a probe designed to capable of accumulating high numbers of mutations recognize a sequence in the 07-71 isolate reacted with in the RNA genome (Holland et al 1982).…”
Section: Bog Codmentioning
confidence: 99%